Examining Brown’s 10 Teaching Factors in the Teaching of English to EFL Learners in the Perspective of Post Method Pedagogy - Haryadi S; Baiq Sumarni (Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
Abstract Ability to operate in English in today’s world is getting more important than ever before. Being capable of using English at workplace becomes influencing factors in fulfilling duties (Clement & Murugavel, 2018). For school teachers, they need to learn English to support careers and to improve personal and professional quality. In EFL context the teaching of English has employed various methods and strategies since long. However, success remains uncertain as these methods, even the latest one so called Communicative Language Teaching (CLT), have been unable to fulfil the needs of EFL learners. In response to this, Post Method is proposed to be an alternative. This paper is trying to examine the implementation of Brown’s 10 teaching Factors to a group of teachers learning English as a foreign language in accordance to the post Method pedagogical theory. Ten non-English teachers, 3 females and seven males, in one of the Indonesian private schools participated in this study. Interview, observation, and questionnaire were used as research instrument to collect data. The finding reveals that before the class commenced, most of the participants hardly understood teachers’ instruction, had poor confidence to speak, and were unable to speak or carry on simple exchange, quite similar to the level of Novice Low, the term coined from Brown (see Brown, 2007, p. 118). However, after 20 class meetings, the participants were able to understand and speak daily conversation, and their speaking confidence increased significantly. Such levels of proficiency very much resemble Novice High and Intermediate Low. This result, however, requires further investigation on the implementation and output of this new teaching concept in different and wider contexts of EFL learners. Key terms: EFL, CLT, Novice Low, Novice Mid, Novice High, Intermediate Low